Body size and risk of MS in two cohorts of US women - Munger, Kassandra L; Chitnis, Tanuja; Ascherio, Alberto (Neurology, 2009)
To examine whether obesity during childhood, adolescence, or adulthood is associated with an increased risk of multiple sclerosis (MS). Women in the Nurses' Health Study (n = 121,700) and Nurses' Health Study II (n = 116,671) provided information on weight at age 18 and weight and height at baseline, from which body mass index was derived. Women also selected silhouettes representing their body size at ages 5, 10, and 20. Over the total 40 years of follow-up in both cohorts combined, we confirmed 593 cases of MS. Cox proportional hazards models, adjusting for age, latitude of residence, ethnicity, and cigarette smoking, were used to estimate the rate ratios and 95% confidence intervals (CI). Obesity at age 18 (body mass index > or =30 kg/m(2)) was associated with a greater than twofold increased risk of MS (multivariate relative risk(pooled) = 2.25, 95% CI: 1.50-3.37, p trend <0.001). After adjusting for body size at age 20, having a large body size at ages 5 or 10 was not associated with risk of MS, whereas a large body size at age 20 was associated with a 96% increased risk of MS (95% CI: 1.33-2.89, p trend = 0.009). No significant association was found between adult body mass and MS risk. Obese adolescents have an increased risk of developing multiple sclerosis (MS). Although the mechanisms of this association remain uncertain, this result suggests that prevention of adolescent obesity may contribute to reduced MS risk.